2015
DOI: 10.1038/sc.2014.213
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating perfusion of thoracic spinal cord blood using CEUS during thoracic spinal stenosis decompression surgery

Abstract: Study design: A clinical study in human spinal cord. Objectives: To evaluate changes in spinal cord blood perfusion in patients with thoracic spinal stenosis using contrast-enhanced ultrasonography and to semiquantitatively analyze blood perfusion changes in compressed spinal cord before and after ventral decompression. Setting: Ultrasound department of a university hospital. Methods: Twelve patients with confirmed thoracic spinal stenosis who needed decompression surgery participated. They underwent an intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A clinical study confirmed that the CEUS-based signal of microbubbles correlates well with blood perfusion in various organs, especially for end-capillary blood 15 . A probe was used to collect and save real-time continuous and dynamic ultrasonographic videos for 1 min after initiation of the injection 16 . The probe must be perpendicular to the spinal cord and avoid touching the dural mater to prevent iatrogenic compression.…”
Section: Methodsmentioning
confidence: 99%
“…A clinical study confirmed that the CEUS-based signal of microbubbles correlates well with blood perfusion in various organs, especially for end-capillary blood 15 . A probe was used to collect and save real-time continuous and dynamic ultrasonographic videos for 1 min after initiation of the injection 16 . The probe must be perpendicular to the spinal cord and avoid touching the dural mater to prevent iatrogenic compression.…”
Section: Methodsmentioning
confidence: 99%
“…What was confusing was that the muscle power of lower limbs started to get paralyzed 10 hours after operation. Though, no similar delayed paraplegia were reported before, the most likely reasons for paraplegia after TES are spinal cord injury, epidural hematoma formation, and spinal cord ischemia [16][17][18]. In operation, special attention was paid to protect spinal cord, all procedures close to it were very careful, and no injury of spinal cord was noticed, which was veri ed by the fact that neurological status immediately after operation was just as the preoperative situation, and intraoperative spinal function monitoring may help identify spinal cord injury in time [19].…”
Section: Discussionmentioning
confidence: 99%
“…Vetrano [30] Human Multi 12 CEUS was used to visualize tumors intraoperatively during removal CEUS allowed surgeons to see perfusion and structure of tumors in real time intraoperatively.…”
Section: Della Pepa [2]mentioning
confidence: 99%
“…Despite this, there have been several studies using this imaging modalities for various other spinal cord pathologies in humans. Ling et al [30] performed a clinical study of 12 patients undergoing surgery for decompression of chronic compressive thoracic vertebrae using CEUS. The authors were looking at time-intensity curves, enhanced intensity of the image, and rise time.…”
Section: Rodent Model Studiesmentioning
confidence: 99%